Female Community Health Volunteers in Community-Based Health Programs of Nepal: Future Perspective - Resham Bahadur Khatri; Resham Bahadur Khatri; Shiva Raj Mishra; Vishnu Khanal (Frontiers Media S.A., 2017)
Nepal's Female Community Health Volunteers (FCHVs) program started in 1988. In the early years of program initiation, FCHVs were assigned to promote and distribute the family planning commodities such as condoms and pills. Over past three decades, FCHVs' roles have gradually expanded beyond family planning program and especially are focused on maternal and child health services at a large scale. FCHVs are an integral part of many community-based health programs, and their roles are instrumental in linking families and communities to community health workers and periphery-level health facilities. However, the fragmented nature of health programs poses a challenge for these health volunteers to coordinate activities and deliver the results. This perspective aims to review their contribution, challenges and recommend an integrated FCHV program model to support in the implementation of the community-based health interventions effectively.